Covalent self-assembly in two dimensions: connecting covalent organic framework nanospheres into crystalline and porous thin films - Sasmal, Himadri Sekhar; Halder, Arjun; Kunjattu, Shebeeb; Dey, Kaushik; Nadol, Athulya; Ajithkumar, Thalasseril G.; Bedadur, Prachiti Ravindra; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
Insolubility of covalent organic frameworks (COFs) in organic solvents is one of the major obstacles for the potential application of these extended networks such as drug delivery, sensing, optoelectronics, and semiconductor device fabrication. The present work proposes a unique way to make uniform, solution-processable, crystalline, and porous COF nanospheres directly from the homogeneous solution of amine and aldehyde via spatial and temporal control of the nucleation and growth. This strategy of direct nucleation simultaneously showcases the caliber to tune the size of the COF nanospheres from 25 to 570 nm. We have also demonstrated the concept of mesoscale covalent self-assembly of those solution-processable COF nanospheres in the liquid-liquid interface (DCM-water bilayer) for the very first time, transmuting them into self-standing COF thin films with long-range ordered arrangements in two dimensions. The crystalline and porous (with TpAzo showing highest S-BET of 1932 m(2) g(-1)) free-standing COF thin films could be fabricated in a wide range of thicknesses from as low as 21 nm to as high as 630 nm. Both beta-ketoenamine (TpAzo, TpDPP) and imine (TpOMeAzo, TpOMeDPP) linked COF thin films have been synthesized via mesoscale covalent self-assembly of the solution-processable COF nanospheres illustrating the generality of this eloquent methodology. Further, the solution processability has been tested and utilized to cast COF thin films uniformly in the inner and outer surface of an alumina hollow fiber membrane. The COF thin film-alumina hollow fiber membrane composites have showcased promising selective molecular separation of He and O-2, He and CO2, and He and N-2.

Fly-ash-based geopolymers: leachability and solid-state NMR investigations - Nadol, Athulya; Ajithkumar, T. G.; Singla, Rashmi; Alex, T. C.; Kumar, Sanjay; Bhatt, Himal; Deo, M. N.; Sen, Debasis; Ambashta, R. D.; Bajpai, R. K.; Shivakumar, Y. C.; Manohar, S. (Bulletin of Materials Science, 2026)
This study aims to explore how leaching impacts the microstructure of a selected fly ash-derived geopolymer and evaluate its potential for near-surface disposal of radioactive waste. The uniqueness of this geopolymer formulation is its ability to form an aluminosilicate network that remains resistant to structural changes upon contact with water. The leach index of base elements such as Ca, Al, Na and Si was between 11 and 13, suggesting that the formulation is superior to Portland cement or conventional hydraulic cement. Solid-state NMR reveals that the water-interacted specimen has no contamination of the zeolite phase and all the Na is incorporated into the aluminosilicate geopolymer gel network, which also confirms that the glassy network of the geopolymer is responsible for imparting low leachability of base elements from its structure, and there is no labile sodium available for exchange as in zeolites.
Keywords: aluminosilicate network; Fly ash; Geopolymers; leaching; Solid-state NMR